Fetal pulmonary venous Doppler patterns in hypoplastic left heart syndrome: relationship to atrial septal restriction. Issue 11 (8th October 2007) - Chintala, K; Tian, Z; Du, W; Donaghue, D; Rychik, J
Abstract : Objective: Pulmonary venous Doppler (PVD) patterns are abnormal in fetuses with hypoplastic left heart syndrome (HLHS) with restricted foramen ovale (rFO) when compared with healthy fetuses. The objective of this study was to define PVD patterns in HLHS fetuses with an unrestricted or patent foramen ovale (pFO). Design: 27 fetuses with HLHS and 66 healthy fetuses underwent echocardiography between 19 and 38 weeks of gestation. The pulmonary venous peak systolic (S), diastolic (D) and atrial reversal (A) velocities were measured; S/D ratio, velocity time integral of forward (VTIf ) and reversed (VTIr ) flows and VTIr expressed as percentage of VTIf (%R) were calculated. Independent examiners classified HLHS subjects into HLHS-pFO and HLHS-rFO (rFO or intact atrial septum). Setting: Tertiary referral centre for paediatric cardiology. Results: Compared with healthy controls, the HLHS-pFO group (n = 16) had higher S (32.9 (3.2) vs 23.5 (1.6) cm/s (adjusted mean (SE)); p = 0.01), A (10.5 (3.4) vs 0.17 (1.6) cm/s; p = 0.01), VTIr (0.78 (0.3) vs 0.01 (0.13) cm; p = 0.01) and %R (14.2% (3.2 %) vs −1.3% (1.5%); p<0.001). D velocity, S/D and VTIf showed no difference. In HLHS-rFO, further increase in S, A, VTIr and %R, decrease in D, increase in S/D and no change in VTIf were noted. Conclusions: PVD flow patterns are abnormal in HLHS even in the absence of rFO, suggesting that factors other than impaired left atrial egress play a role. Future studies of PVD patterns can provide important insights into left atrial dynamics, pulmonary venous return and pulmonary vascular development in fetal HLHS.